2020
DOI: 10.2147/rmhp.s265887
|View full text |Cite
|
Sign up to set email alerts
|

<p>Estimation of Generalized Impact Fraction and Population Attributable Fraction of Hypertension Based on JNC-IV and 2017 ACC/AHA Guidelines for Cardiovascular Diseases Using Parametric G-Formula: Tehran Lipid and Glucose Study (TLGS)</p>

Abstract: An area of interest to health policymakers is the effect of interventions aimed at risk factors on decreasing the number of new cardiovascular disease (CVD) cases. The aim of this study was to estimate the generalized impact fraction (GIF) and population attributable fraction (PAF) of hypertension (HTN) for CVD in Tehran. Patients and Methods: In this population-based cohort study, 8071 participants aged ≥30 years were followed for a median of 16 years. A survival model was used to estimate the 10-and 18-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Strikingly, it has been reported that a 10 mmHg lower SBP is associated with a 30–40% lower risk of stroke [32]. In addition, based on the 2017 ACC/AHA guideline, by a 30% reduction in the prevalence of hypertension, 6.1% of CVD cases could be prevented [33]. Also, in 2016, the approximate rate of Iranian participants who were aware of their hypertension were estimated at 37.1% regarding the 2017 ACC/AHA guidelines [24].…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, it has been reported that a 10 mmHg lower SBP is associated with a 30–40% lower risk of stroke [32]. In addition, based on the 2017 ACC/AHA guideline, by a 30% reduction in the prevalence of hypertension, 6.1% of CVD cases could be prevented [33]. Also, in 2016, the approximate rate of Iranian participants who were aware of their hypertension were estimated at 37.1% regarding the 2017 ACC/AHA guidelines [24].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, Mansournia and colleagues applied MBS in case-control studies and parametric g-formula in cohort studies in the fixed and time-varying settings. 23 , 70 - 74 …”
Section: Discussionmentioning
confidence: 99%
“…Considering the ideal world where it is not practically feasible to completely eliminate HIV exposure, we calculated generalized impact fractions (GIF) to assess the benefits of reducing the prevalence of HIV by 1%, 20%, 40%, 60%, 80%, and 100% in preventing NHL. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%